2018
DOI: 10.1111/jcpp.12951
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐directional longitudinal associations between different types of bullying victimization, suicide ideation/attempts, and depression among a large sample of European adolescents

Abstract: The results support the bidirectional effect of victimization and depression and indicate that there are complex longitudinal associations between victimization and suicidal ideation/attempts. Physical victimization may especially carry effect on suicidal risk over time. Interventions should focus on victimization as a cause of distress but also aim to prevent vulnerable adolescents from becoming targets of victimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 38 publications
8
72
1
9
Order By: Relevance
“…Consistent with the internalizing behaviors as potential determinants of SPR and general interaction principles in our model, such behaviors in youth have been conceptualized as having an interpersonal etiology (Epkins and Heckler, 2011;Madigan et al, 2013). Further, in line with victimization as an important component of the peer environmental plane as discussed below, longitudinal results stipulate a role of victimization in both short-lived and persistent internalizing symptoms (Zwierzynska et al, 2013;Brendgen and Poulin, 2018) linked to suicidal ideation and suicide attempts (Brunstein Klomek et al, 2019;Hinduja and Patchin, 2019). Conversely, SPR have a protective role in the relationship between the negative mental health outcomes of victimization and suicidal ideation (Jenkins et al, 2018).…”
Section: Behavior and Health As A Peripheral Self-building-blocksupporting
confidence: 65%
“…Consistent with the internalizing behaviors as potential determinants of SPR and general interaction principles in our model, such behaviors in youth have been conceptualized as having an interpersonal etiology (Epkins and Heckler, 2011;Madigan et al, 2013). Further, in line with victimization as an important component of the peer environmental plane as discussed below, longitudinal results stipulate a role of victimization in both short-lived and persistent internalizing symptoms (Zwierzynska et al, 2013;Brendgen and Poulin, 2018) linked to suicidal ideation and suicide attempts (Brunstein Klomek et al, 2019;Hinduja and Patchin, 2019). Conversely, SPR have a protective role in the relationship between the negative mental health outcomes of victimization and suicidal ideation (Jenkins et al, 2018).…”
Section: Behavior and Health As A Peripheral Self-building-blocksupporting
confidence: 65%
“…This seems to indicate that anxiety and depression are more affected by both types of bullying than general HRQoL. Previous studies have demonstrated how bullying and homophobic bullying are highly related to mental health deterioration in youth [53,58], fundamentally if the victimization becomes chronic [59]. As in the case of HRQoL, it seems that traditional bullying has a higher negative impact in mental health than homophobic verbal content bullying, attending the levels of depression and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…The struggle in choosing either self-killing or living might contribute to frequent psychological stress that finally leads to depression, and the reverse might be true. 45,46…”
Section: Discussionmentioning
confidence: 99%